1960
DOI: 10.1007/bf01250677
|View full text |Cite
|
Sign up to set email alerts
|

Observations on immunological tolerance and ?Immunity? in mice infected congenitally with the virus of lymphocytic choriomeningitis (LCM)

Abstract: Mice infected in utero with LCM virus carry large amounts of active virus in their blood and organs for many months and discharge considerable quantities of the agent with their secretions and excretions (11). This observation indicates continuous multiplication of the virus in the organs of such animals, which look like normal individuals in spite of their chronic infection. Intrauterine infection leads to a stable equilibrium between virus and body. It was also observed that mice infected in utero would deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1961
1961
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Mice: The tolerant animals came from our infected stock mentioned previously (11) in which all mice, young or old, are carriers of strain W of LCM virus. The mice immunized as mature animals and the controls were obtained from stock III of the Institute (ill from which the ancestors of the infected colony originated.…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice: The tolerant animals came from our infected stock mentioned previously (11) in which all mice, young or old, are carriers of strain W of LCM virus. The mice immunized as mature animals and the controls were obtained from stock III of the Institute (ill from which the ancestors of the infected colony originated.…”
Section: Virusesmentioning
confidence: 99%
“…Although such mice are not tolerant immunologically, they form neutralizing antibodies rather poorly (4, 10). Since many of them do not carry demonstrable amounts of infectious virus in their brains and other organs (5, 4), there w~s at first no reason to suppose that their immunity might be correlated with the interference phenomenon, which appears to be responsible for the strong immunity of tolerant mice (virus carriers) infected congenitally with LCM virus (7,11).It is the purpose of this communication to show that slight but definite interference with EEE virus occurs in the brains of both categories of LCM-immune mice and that the persistence of detectable quantities of infectious LCM virus is not a prerequisite for such interference in nontolerant animals. …”
mentioning
confidence: 97%
“…Although it has often been stated that LCM virus does not induce interferon (19)(20)(21)(22), it has recently been shown that this virus is an excellent interferon inducer in suckling and adult mice (23)(24)(25)(26). We postulated, therefore, that the endogenous interferon induced by LCM virus in the neonatal period (26) was in part responsible for this syndrome.…”
mentioning
confidence: 94%
“…Elimination of virus is likewise a slow process and viraemia may remain detectable for a long time. A few mice seem to retain traces of infectivity for months and presumably for life (Traub, 1938;Haas, 1954;Rowe, 1954;Traub, 1961;Lehmann-Grube, 1964a;Volkert, 1964;Volkert and Lundstedt, 1968;Larsen, 1969c). Although some neutralizing antibody can be detected in mice which have survived infection, elimination of the virus does not appear to be mediated by circulating antibody and is probably accomplished by cellular mechanisms.…”
mentioning
confidence: 99%
“…A few mice inoculated right after birth and found to be carriers have been later found to be free of virus (Lehmann-Grube, 1964b) but this does not appear to happen with congenital carriers (Lehmann-Grube, to be published). In addition to showing infectivity, all tissues contain CF antigen (Traub, 1961). As a result of a cooperative study conducted with my colleague, Dr H. Gschwender, it has been shown that most, if not all, antigens with CF activity are initially bound to membranous structures of the cells.…”
mentioning
confidence: 99%